Abolishing military and cultivating pacifism in Costa Rica: reflective but limited peace? - Mohd Firdaus, A. J. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Existing literature on peace, security and civil-military relations in Latin America only recently recognises the historical institutional sources of Costa Rican exceptionalism. While the Cold War's security predicament and the military dictatorship are common antecedents for most Central American states, Costa Rican demilitarisation and pacifism origins are unique and incomparable. Rather than treating post-1948 civil war development as exceptionalism, this paper seeks to normalise their success. The paper examines the political development of Costa Ricans in the 1950s and whether José María Hipólito Figueres Ferrer's historic decision to permanently abolish the military after the war helped to explain the institutionalisation process of organic civilian peace. This article reinvigorates Costa Rican exceptionalism. It analyses the cultivation of pacificism of those that have made the right choices in the face of adverse circumstances. The path dependence on national progress in education, health, and productivity only confirmed the unique political trajectory of Costa Rica, wherein they cannot be easily replicated or comparable. Understanding this distinctiveness should serve as a reminder of any renewed debate of Costa Rican exceptionalism in Central American security or democratic peace theory in liberal peacebuilding.